REPRESENTASI GAYA HIDUP HEDONISME GENERASI MILLENIAL DALAM MEDIA SOSIAL INSTAGRAM - Dhiya Izzahtul Zayyan; Abd. Majid; Zelfia Zelfia (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2020)
The purpose of this study was to find out the representation of hedonism in millennials' instagram social media, especially on the instagram accounts of @Trimurtivirjinia, @aldigeraldine_, @intanrwidhi, @Touchup.byaber and @Icalieemmm and how the form of satisfaction behavior shown in the instagram account of millennials as a representation of hedonism lifestyle. This research uses qualitative research methods with semiotic analysis based on the theory of television codes by John Fiske which is divided into three levels; That is the level of Reality, the level of Representation, and the level of Ideology and consumptive theory fromm. Research is conducted by data collection through observation (mechanics), documentation and interviews. This research lasted for one month and was located in Makassar City. The results showed that at the level of reality their appearance was judged to show a life of luxury and always having fun. Hedonism is seen in aspects of appearance, costume, makeup, environment, behavior, way of speaking, movement, and expression in the instagram social media spotlight. At the ideological level there are codes through their uploads that have been determined by researchers. That is, like, like to buy things that are luxurious and branded and usually not useful. With the form of satisfaction behavior shown in his lifestyle they do excessive behavior justifying all means in maintaining appearance and maintaining his image without thinking again whether this is useful or not.